Sampling and approximation techniques for efficient process conformance checking. Issue 104 (February 2022) - Bauer, Martin; van der Aa, Han; Weidlich, Matthias
Abstract: Conformance checking enables organizations to automatically assess whether their business processes are executed according to their specification. State-of-the-art conformance checking algorithms perform this task by establishing alignments between behaviour recorded by IT systems to a process model capturing desired behaviour. While such alignments clearly highlight conformance issues, a major downside is that these algorithms scale exponentially in the size of both the event data, capturing recorded behaviour, and the process model used as input. At the same time, it is crucial to recognize that event data used for such analyses typically only relates to a specific interval of process execution rather than the entire history, meaning that the employed event data is inherently incomplete. Therefore, we argue that statistical methods allow one to obtain a proper understanding of the overall conformance of a process by considering only a fraction of the available data. In this paper, we therefore present a statistical approach to conformance checking that employs trace sampling and result approximation in order to derive conformance results in an efficient manner. The approach reduces the runtime significantly, while still providing guarantees on the accuracy of the estimated conformance result. We instantiate the general approach for different measures of the overall conformance of an event log and a process model, including fitness as a direct quantification of conformance as well as the distribution of deviations over activities and deviations related to contextual factors, such as the involved resources. Moreover, to increase the robustness of our approach, we elaborate on mechanisms to reveal biases in sampling procedures. Experiments with real-world and synthetic datasets show that our approach speeds up state-of-the-art conformance checking algorithms by up to three orders of magnitude, while largely maintaining the analysis accuracy. Highlights: We propose sample and approximation-based techniques for conformance checking. Cover three types of conformance measures, fitness, deviations, and resources. Experiments show that runtime efficiency is increased by orders of magnitude.